Thomas Piketty, A Brief History of Equality. Colombia: Editorial Ariel, 2022. 294 pages. - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2023)
Thomas Piketty, A Brief History of Equality